Adsorption of the rare earth elements cerium, lanthanum, and neodymium onto ZSM-5 zeolite: A statistical physics approach (2024)
The recovery of rare earth elements (REE) is essential to meet the growing demand for these resources and promote the reuse of available resources. This study investigated the potential of ZSM-5 zeolite in the recovery of trivalent ions of cerium, lanthanum and neodymium under conditions of pH 6 and temperatures between 298 and 328 K. REE equilibrium isotherms were analyzed using five statistical physics models. The results indicate that removing all REE occurs predominantly in monolayers, as these models showed better prediction performance (coefficient of determination > 0.97 and mean squared error < 18.0). The best model determined that lanthanum and neodymium have one adsorption energy, while cerium has two adsorption energies involved in the process. The predominant functional groups are those containing silicon. Increasing temperature causes an increase in the number of REE ions captured per functional group, which reduces the adsorption space available on the surface. The model parameters indicate that the adsorption of these ions implies a multi-ionic mechanism (number of ions adsorbed per site greater than 1) and is an exothermic process. Based on the calculated adsorption capacities at saturation, the order of preference in adsorption can be established: neodymium > cerium > lanthanum. The adsorption energies indicate that the process occurred mainly due to physical forces since all energy values are below 40 kJ mol−1. The study’s results led to the proposal of a mechanism for the adsorption of REE on ZSM-5 zeolite, which highlights the predominance of electrostatic interactions and complex formation, which result in the formation of a monolayer on the adsorbent’s surface.